Biomedical research goes viral: dangers and opportunities - Zeggini, Eleftheria; Baumann, Michael; Götz, Magdalena; Herzig, Stephan; Hrabě de Angelis, Martin; Tschöp, Matthias (Cell, 2020)
Researchers around the globe have been mounting, accelerating, and redeploying efforts across disciplines and organizations to tackle the SARS-CoV-2 outbreak. However, humankind continues to be afflicted by numerous other devastating diseases in increasing numbers. Here, we outline considerations and opportunities toward striking a good balance between maintaining and redefining research priorities.